P-142 The Effects of Environmental Enrichment, Social Housing and Gender on Intestinal Tumorigenesis in a Murine Model of Colon Cancer. (March 2016) - Lang, Jessica; Santaolalla, Rebeca; Dheer, Rishu; Davies, Julie; Phillips, Matthew; Grant, Jeff; Zaias, Julia; Abreu, Maria
Abstract : Background: Colorectal cancer is a widespread disease that affects 130, 000 people annually in the US alone. Colitis-associated cancer can be modeled in mice by treating them with a combination of the genotoxic agent azoxymethane (AOM) and the colitis inducer dextran sodium sulfate (DSS). The primary aim of this study was to see if environmental enrichment, social housing and gender have an effect on intestinal tumorigenesis, using the AOM-DSS murine model. Methods: We used aged matched C57BL/6J (n = 64) mice that were randomly assigned to groups, each having an equal number of males and females. Mice were housed either singly or in groups (4 mice/cage) as a model for social housing. Nestlets were provided to half of the mice as a means of environmental enrichment. AOM-DSS treatment was administered to all groups. Mice were given an intraperitoneal injection of AOM (14.6 mg/kg) on day one of the study. On day 14, mice were administered a cycle (7 days) of 3% DSS. Following this, mice were given 2 weeks of recovery time and subsequently treated with a second cycle of 3% DSS for an additional 7 days. We measured the outcome of these conditions by counting tumor number, measuring tumor load (number of tumors × diameter taken at the longest point), and examining histological inflammatory and neoplastic changes between the groups. We also examined the welfare of the animals by recording nest scores over the course of the treatment. Results: We found that socially deprived animals (n = 24) get higher numbers of tumors ( P < 0.05), and also had an increased tumor load ( P < 0.05) compared to their group housed counterparts (n = 32). Tumor number and load were also significantly higher in female mice, especially when singly housed ( P < 0.05). Average nest scores were highest among the single housed animals, particularly in female mice. Environmental enrichment had no effect in tumorigenesis. Conclusions: Although environmental enrichment had no effect in tumorigenesis, grouping and gender both had an impact. These results are important regarding recommendations for the use of both social housing and sex selection for animal sampling in tumor models. Ultimately this study has showed that social housing and sex influence rodent welfare, revealing the importance of selecting proper environmental and housing conditions, specifically in models of colitis-associated neoplasia.